Squirmer dynamics in viscoelastic media at low Reynolds number: From individual motion to collective order - Zhou Yuan; Qi Kai (EPJ Web of Conferences)
The locomotion of microswimmers in viscoelastic fluids plays a fundamental role in both biological systems and synthetic active matter. In this study, we examine the dynamics of model squirmers immersed in polymeric fluids under low Reynolds number conditions using a hybrid Lattice Boltzmann framework. At the single-squirmer level, we report a significant enhancement of rotational diffusion resulting from squirmer– polymer interactions. Pullers exhibit the strongest enhancement, up to 118- fold compared to passive colloids, due to asymmetric flow fields and polymer accumulation at the rear. Pushers show moderate enhancement (approximately 90-fold), primarily caused by weak polymer wrapping at the front. In contrast, neutral squirmers only show 18-fold enhancement, as their symmetric flow rapidly advects polymers away from the squirmer surface. Translational motion is generally reduced for all squirmer types due to increased rotational decorrelation and polymer-induced viscous resistance. The analysis is extended to many-body squirmer suspensions, revealing that polymer-mediated interactions significantly influence collective alignment. For pullers, the polarization strength increases by approximately 21% at a polymer concentration φp = 0.16 , driven by a bidirectional feedback mechanism between squirmer-induced polymer stretching and flow modification through polymer alignment. In contrast, neutral squirmers exhibit reduced polarization due to weaker hydrodynamic feedback, while pushers remain largely unaffected. These findings highlight the pivotal role of viscoelastic microstructures in shaping both individual and collective microswimmer behavior and offer a foundation for future studies on the effects of active stresses, thermal fluctuations, and polymer deformation in active matter systems.